Between Metropole and Province: circulating botany in British museums, 1870–1940. Issue 1 (April 2020) - Cornish, Caroline; Allan, Patricia; Gardiner, Lauren; Nicol, Poppy; Pardoe, Heather; Sherwood, Craig; Webster, Rachel; Young, Donna; Nesbitt, Mark
Abstract : Exchange of duplicate specimens was an important element of the relationship between metropolitan and regional museums in the period 1870–1940. Evidence of transfers of botanical museum objects such as economic botany specimens is explored for the Royal Botanic Gardens, Kew, and six museums outside the capital: Cambridge University Botanical Museum, National Museum Wales, Glasgow Museums, Liverpool World Museum, Manchester Museum and Warrington Museum. Botany became an important element in these museums soon after their foundation, sometimes relying heavily on Kew material as in the case of Glasgow and Warrington, and usually with a strong element of economic botany (except in the case of Cambridge). Patterns of exchange depended on personal connections and rarely took the form of symmetrical relationships. Botanical displays declined in importance at various points between the 1920s and 1960s, and today only Warrington Museum has a botanical gallery open to the public. However, botanical objects are finding new roles in displays on subjects such as local history, history of collections, natural history and migration.